1998
DOI: 10.1002/(sici)1097-4636(199808)41:2<270::aid-jbm12>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyelectrolyte complex (PEC) on human periodontal ligament fibroblast (HPLF) function. II. Enhancement of HPLF differentiation and aggregation on PEC by L-ascorbic acid and dexamethasone

Abstract: In addition to many types of extra cellular matrix (ECM) in vivo, cells are stimulated by many types of vitamins, hormones, growth factors, etc. In this paper the effects of L-ascorbic acid 2-phosphate (Asc-2P) and dexamethasone (Dex) on proliferation and differentiation of human periodontal ligament fibroblast (HPLF) using polyelectrolyte complex (PEC) as a matrix in vitro will be discussed. The PEC was composed of chitosan as a polycation, with carboxymethyl (CPEC) or sulfated chitin (SPEC). Asc-2P (0.2 mM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…In vivo, chitosan were shown to decrease fibroblast infiltration and fibrosis [19], reduct the quantity of ECM deposition and degrade collagen synthesis to an appropriate rate [20][21][22]. In addition, chitosan can also stimulate reepithelialization in experimental wounds [23].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, chitosan were shown to decrease fibroblast infiltration and fibrosis [19], reduct the quantity of ECM deposition and degrade collagen synthesis to an appropriate rate [20][21][22]. In addition, chitosan can also stimulate reepithelialization in experimental wounds [23].…”
Section: Introductionmentioning
confidence: 99%
“…These facts agree with our previous report; the cell specific function, proliferation and differentiation of in vitro cultured cells using a polyelectrolyte complex as a matrix, could be controlled by a kind and quantity of anionic residues, carboxyl and/or sulfate groups, of anionic polysaccharides. [12,13,21] We found that S-HA had high immunological safety as well as HA and other natural polysaccharides, as a medical material. Moreover, by controlling D.S.…”
Section: The Inhibitory Effect Of S-ha On Histamine Release Induced Bmentioning
confidence: 92%
“…And, we have already cleared up that a kind and quantity of anionic groups, carboxylic (-COOH) or sulfuric acid (-SO 3 H) groups, controlled cell functions cultured on polyelectrolyte complex (PEC) in vitro. [12,13] Therefore, in this study, we synthesized sulfated HA (S-HA) with various degrees of substitution and high molecular weight, which size is not the same as natural sulfated polysaccharides, in order to give HA new biological functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PECs have generated much interest in medical and drug fields for applications such as catalysts, binding of pharmaceutical products, isolation and fractionation of proteins, and isolation of nucleic acid 6, 7. There are several reports that PEC membranes have excellent biocompatibility, and can control periodontal ligament cells' and osteoblasts' adhesion, growth, and morphology 8–12…”
Section: Introductionmentioning
confidence: 99%